The Role of Dhikr and Prayer Council Shaping Religious Morals: A Case Study of Sholawat Mahabbatur Rosul - Purwanto (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
This research was motivated by the existence of problems faced by teenagers in the Padang Sari village environment. In this rampant deviant behaviour, the existence of the Mahabbatru Rosul dhikr and prayer science council became a forum for conditioning and a medium for instilling moral values for teenagers. This study aims to determine the role and inhibiting factors of the Mahabbatur Rosul dhikr and sholawat assembly in forming the religious morals of adolescents. This research is descriptive qualitative research with a field research design and uses an ethnographic approach. The data in the study were obtained through interviews, documentation, and direct observation in the field. The location of this research is the house of Mahabbatur Rosul's Dhikr and Prayer Science Council. This research is analysed using Erving Goffman's dramaturgical approach. The results of the research show that active participation in Mahabbatur Rosul's dhikr and prayer science assembly plays a role in the formation of adolescent religious morals through the activities carried out, namely: (1) learning to read the al-Qur’an and recitation, (2) learning Safinah fiqh, and (3) the Friday night routine. Through these activities, teenagers' religious morals will be formed, making them more careful in their actions. This research concludes that Mahabbatur Rosul's collection of dhikr and prayer plays a role in the formation of adolescent religious morals through all the activities carried out. The religious morals that are formed by the Messenger are honesty, responsibility, and discipline.